The invisible reality: English teaching materials and the formation of gender and sexually oriented stereotypes (with a focus on primary education) - Pellicer Ortín, Silvia; Asín Abad, Alicia (Complutense Journal of English Studies, 2018)
Gender stereotypes, understood as those structured sets of beliefs about personal attributes of women and men, have a great influence over self-perspective and the social interaction and organisation. However, their effects are sometimes invisible, and a great effort should be made to develop awareness of their influence in the population. Our main claim is that School has an essential role to teach gender and sexual equality through the curricula, using teaching materials that are free of these stereotypes. The main aim of this study is to examine the presence of gender and sexually oriented stereotypes in various English teaching materials within the context of the Spanish Primary School, focusing on its last stage. This research carries out a qualitative and quantitative analysis of three English textbooks together with the students’ and teachers’ perceptions of gender stereotypes. The analysis is done thanks to the review of key concepts, such as gender awareness and sexual identity, as well as the presentation of various examination tools that have allowed us to evaluate the sexist content in the textbooks selected and offer some guidelines to avoid them in the English classroom.